2016
DOI: 10.3390/s16020265
|View full text |Cite
|
Sign up to set email alerts
|

Fast, Highly-Sensitive, and Wide-Dynamic-Range Interdigitated Capacitor Glucose Biosensor Using Solvatochromic Dye-Containing Sensing Membrane

Abstract: In this paper, we proposed an interdigitated capacitor (IDC)-based glucose biosensor to measure different concentrations of glucose from 1 μM to 1 M. We studied four different types of solvatochromic dyes: Auramine O, Nile red, Rhodamine B, and Reichardt’s dye (R-dye). These dyes were individually incorporated into a polymer [polyvinyl chloride (PVC)] and N,N-Dimethylacetamide (DMAC) solution to make the respective dielectric/sensing materials. To the best of our knowledge, we report for the first time an IDC … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
3

Relationship

3
5

Authors

Journals

citations
Cited by 22 publications
(12 citation statements)
references
References 39 publications
0
12
0
Order By: Relevance
“…The response as well as recovery time were approximately 12.92 s and 13.3 s, respectively. In [ 91 ], we reported for the first time an IDC-based glucose biosensing system which had a sensing/dielectric membrane containing a solvatochromic dye. The glucose biosensing system had a single channel, and the proposed IDC glucose biosensing system has a faster sensing response than the lipid-based IDC taste sensing system and its response and recovery times were about 7 s and 5 s respectively.…”
Section: Resultsmentioning
confidence: 99%
“…The response as well as recovery time were approximately 12.92 s and 13.3 s, respectively. In [ 91 ], we reported for the first time an IDC-based glucose biosensing system which had a sensing/dielectric membrane containing a solvatochromic dye. The glucose biosensing system had a single channel, and the proposed IDC glucose biosensing system has a faster sensing response than the lipid-based IDC taste sensing system and its response and recovery times were about 7 s and 5 s respectively.…”
Section: Resultsmentioning
confidence: 99%
“…The pulse generator/modulation [47,48,49] unit consists of three units: a square-wave generator, a buffer amplifier, and a laser diode (LD) driver with LD. The square-wave generator produces a square wave with a frequency of 10 kHz and a 50% duty cycle.…”
Section: Methodsmentioning
confidence: 99%
“…To do this, Nile red and rhodamine-B were individually dissolved into different pH (2–12) of buffer solution to make 10 mM of Nile red and rhodamine-B containing pH solution, then we observed the absorption peak of those dyes containing pH solutions and we found that as the pH of a Nile red/rhodamine-B containing pH buffer solution increases, the absorption peak of the Nile red/rhodamine-B containing pH solution increases as well. The experimental setup of this experiment is discussed in detail in [48]. This occurs owing to a change in the refractive index of dye containing pH solution.…”
Section: Methodsmentioning
confidence: 99%
“…For detection of 4-nitrophenol, manganese dioxide/ reduced graphene oxide nanocomposite paper was fabricated for supercapacitor preparation [8]. Using the interdigitated electrode capacitors, glucose, based on solvatochromicdye-containing sensing membrane [9], and foodborne pathogenic Escherichia coli [10] were detected. A supercapacitor-based biosensor for low lipoprotein detection was also proposed [11].…”
Section: Introductionmentioning
confidence: 99%